PERSEPSI JEMAAT TENTANG KAUM DISABILITAS DAN AKSES MEREKA KE DALAM PELAYANAN GEREJA - Harisantoso, Imanuel Teguh (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
This study explores the congregation's understanding of disability and their access to church services. The research subjects are taken from 53 congregations spread over 18 synods. The methodology used is descriptive qualitative with data collection techniques through open interviews, visiting participants directly, and communication technology media for participants who are not reached face to face. Six informants were involved in each congregation, consisting of one pastor and five church council members. The study suggests that churches view disability as stereotyping, stigmatizing, and harmful. The Church provides opportunities for disability involvement in ministry but in minimal opportunities. It provides normality criteria for people with disabilities to be able to serve. CHURCH MEMBERS PERCEPTION OF PEOPLE WITH DISABILITIES AND THEIR ACCESS TO CHURCH SERVICES.